Anodal tDCS Over the Left Prefrontal Cortex Does Not Cause Clinically Significant Changes in Circulating Metabolites - Kortteenniemi, Aaron; Ortega-Alonso, Alfredo; Javadi, Amir-Homayoun; Tolmunen, Tommi; Ali-Sisto, Toni; Kotilainen, Tuukka; Wikgren, Jan; Karhunen, Leila; Velagapudi, Vidya; Lehto, Soili M. (Frontiers in Psychiatry, 2020)
Background: Transcranial direct current stimulation (tDCS), a putative treatment for depression, has been proposed to affect peripheral metabolism. Metabolic products from brain tissue may also cross the blood-brain-barrier, reflecting the conditions in the brain. However, there are no previous data regarding the effect of tDCS on circulating metabolites. Objective: To determine if 5 daily sessions of tDCS modulate peripheral metabolites in healthy adult men. Methods: This double-blind, randomized controlled trial involved 79 healthy males (aged 20–40 years) divided into two groups, one receiving tDCS (2 mA), the other being sham stimulated. The anode was placed over the left dorsolateral prefrontal cortex, and the cathode over the corresponding contralateral area. Venous blood samples were obtained before and after the first stimulation session, and after the fifth stimulation session. Serum levels of 102 metabolites were determined by mass spectrometry. The results were analysed with generalised estimating equations corrected for family-wise error rate. In addition, we performed power calculations estimating sample sizes necessary for future research. Results: TDCS-related variation in serum metabolite levels was extremely small and statistically non-significant. Power calculations indicated that for the observed variation to be deemed significant, samples sizes of up to 11000 subjects per group would be required, depending on the metabolite of interest. Conclusion: Our study found that 5 sessions of tDCS induced no major effects on peripheral metabolites among healthy men. These observations support the view of tDCS is a safe treatment, and do not support the previously suggested modulatory impact on peripheral metabolic processes.